PENGEMBANGAN MAJALAH IPA BERBASIS KEARIFAN LOKAL PANTAI GOA PETAPA TERHADAP MOTIVASI BELAJAR SISWA - Salsabila, Mezaluna Deazuri; Wahyuni, Eva Ari; Tamam, Badrud; Putera, Dwi Bagus Rendy Astid; Sutarja, Maria Chandra (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2024)
Learning will be more meaningful when it is linked to local wisdom and not just focused on the teacher to motivate students. One of the potential local wisdoms on Madura Island is Goa Petapa Beach, which deserves to be an inspiration for the development of the learning process in the form of a science magazine. This study aims to determine the feasibility, student-learning motivation, and student response to the science magazine using the classification of living things based on the ADDIE developmental model. The research sample consisted of students of Class VII-B, SMPN 1, Tanjung Bumi. The research instruments used include media validation, materials, a motivation questionnaire, and a student response questionnaire. The results showed averages: (1) media expert validation of 1.00 (very high category); (2) material expert validity of 1.00 (very high category); and (3) student learning motivation of 78.44% (high category), so it can be concluded that science magazines are suitable for use in learning and can motivate students